Review of “Discourses of Globalisation, Cultural Diversity and Values Education” by Joseph Zajda - Sylvia, Novi; Yustiana, Yusi Riksa (International Journal of Educational Review, 2024)
This study aims to analyze the concepts in the book “Discourses of Globalisation, Cultural Diversity, and Values ​​Education” by Joseph Zajda (2023). The method used in this study is a book review, in which the researcher  summarizes each chapter of the book and identifies the primary approaches, namely Bronfenbrenner's Bioecological Model, Bandura's Social Learning Theory, Vygotsky's Language Development Theory, and James Banks' Multicultural Education Model. These approaches provide a theoretical basis for understanding multiculturalism's importance in guidance and counseling. The emphasis on (1) the positioning of education amid globalization and cultural diversity and (2) the formation of value education in schools based on how the school forms the value itself are the main implications of this finding. These implications reinforce the importance of value education in promoting cross-cultural understanding and enriching insights into the influence of the social environment to enhance the knowledge of how external factors shape individual development and identity. These findings provide practical guidance for counselors to be more responsive to the needs of clients from different cultural backgrounds. Education practitioners or counselors should position the education along with the diversity of the students with the basic principles of equality, democracy, and social justice, and be recommended to further explore the values education suitable to be implemented in the multiculturalism scheme of Indonesia.